Mining for culture : performance arts center Ställberg’s Mine - Berg, Lovisa; Crona, Per (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2013)
This degree project summarizes five years of education at the landscape architecture program at the Swedish University of Agriculture Sciences, SLU, Alnarp and the School of architecture at Royal Institute of Technology, KTH, Stockholm. The project has been carried out by Lovisa Berg and Per Crona in collaboration with DRIFT Scenkonst. This master project is based on the ongoing transformation of a former mining site in Ställberg, Bergslagen situated in central Sweden.